Meningkatkan Hasil Belajar PKN Pada Materi Nilai Dan Norma Sosial Melalui Pembelajaran CIRC (Cooperative, Integrated, Reading, And Composition) Pada Siswa Kelas X Multimedia SMK Negeri 3 Watampone Kabupaten Bone - harniyati harniyati (Universitas Negeri Makassar, 2019)
This research is a classroom action research aimed at improving student learning outcomes in Civics lessons taught through CIRC learning models (Cooperative, Integrated, Reading and Composition) in Multimedia Class X Students of SMK Negeri 3 Watampone Kab. Bone with 35 students. The implementation of this action consists of two cycles, each cycle carried out through the stages of planning, action, observation, and reflection. Data collection techniques used are the provision of tests and observation sheets. The results of the analysis obtained were changes in behavior of students who experienced an increase with the percentage in the first cycle only 94.2% and in the second cycle increased to 95.71% there was also an increase in attention, interest and motivation of students towards the subject matter given by the teacher. From this analysis, it can be concluded that the learning outcomes of PKn students in Class X Multimedia at SMK Negeri 3 Watampone have increased after being given action through the CIRC learning model (Cooperative, Integrated, Reading and Composition).